"A onça braba que vigia a mata nunca dorme”: a cooperação e organização sociopolítica dos Matsés frente às ameaças ao território ancestral entre a fronteira do Brasil e Peru - Furtado, Jaiandra Maina Queiroz (2024)
Along the border between Brazil and Peru, the Matsés ethnic group resides, despite traditionally inhabiting the recently demarcated areas, the Vale do Javari Indigenous Land, in Brazil, and the Yavarí Tapiche Indigenous Reserve, in Peru, the Matsés historically resist threats to its territory. The resistance is due to the concession of plots of land for oil exploration in this border region. Through international cooperation, the Matsés took up struggle and resistance to invasions, so that they organized themselves socially and politically on both sides of the border. The title of the work contains the phrase “The wild jaguar that watches the forest never sleeps” because we understand that it carries great meaning for the Matsés people, also known as Povo Onça. The expression was used during the IV Matsés Brasil Peru Binational Meeting, by an indigenous leader of the ethnic group, precisely, to make it clear that his people are always alert and ready to defend the territory, like a jaguar that watches over the forest. The research aims to analyze how contemporary state structures perpetuate or propagate necropolitics regarding the Matsés located along the Brazil/Peru border; Identify, through the collected documents, which main socio-political means were used for international cooperation between the Matsés peoples and strengthen debates on the indigenous issues of cross-border peoples, as this concerns the social and political ordering of the Matsés in the face of the risk of loss of the territory to which they belong in a physical, cultural and identity way. This is an Exploratory and Descriptive Research, essentially qualitative, which will be carried out through historical bibliographic studies and documentary analysis, through investigation it will be verified whether, through cooperative and resistance actions, the Matsés obtained significant results in terms of oil exploration. in protected territories.